Aminated porous carbon material, method for preparing the same, and use thereof
Patent Information
- Application Number
- CN202510415685.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-04-03
AI Technical Summary
这些常用的化学活化技术多采用过多的强腐蚀性活化剂,易造成设备严重腐蚀、污染环境
[0018](1)利用干燥的中药渣具有的吸湿性,将活化剂吸附达到材料体相内,保证了活化造孔的高效性,同时也降低了活化剂的使用量;这有效降低了经成本和强碱对环境的危害。
Smart Images

Figure CN120247019B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of capacitor desalination and supercapacitors, specifically to an aminated porous carbon material, its preparation method, and its applications. Background Technology
[0002] Electric double-layer capacitance is a highly reversible and efficient ion adsorption behavior, and it is the main working mechanism in supercapacitors (SC) and seawater desalination (CDI). Specifically, under the influence of an applied electric field, a large number of positive and negative charges accumulate on the surfaces of the two electrodes, adsorbing positive and negative ions from the solution between the electrodes to achieve charge balance. In supercapacitors, this behavior is used for charge storage, offering advantages such as fast charging and discharging rates and high reversibility. In desalination, electric double-layer capacitance can adsorb a large number of salt ions to achieve desalination. Of course, the actual efficiency of electric double-layer capacitance depends on various factors, with the performance of the electrode materials being the key limiting factor.
[0003] High specific surface area carbon materials are typical electrode materials exhibiting capacitive behavior, showing promising applications in supercapacitors and capacitor desalination. The development and design of low-value biological waste as carbon sources has always been a research hotspot in this field. As the birthplace of traditional Chinese medicine, plant-based Chinese medicinal materials are widely used in China. Generally, medicinal herb residue is a mixture of various plant residues, making classification and screening impractical and unreasonable. Furthermore, considering the toxicity of medicinal herbs, their treatment has always been of negative economic value. Compared to using them as low-value fuel, converting them into high-value capacitor materials has greater development potential and research value. Considering the differences in nanostructure and composition among different medicinal herb residues, the challenge in converting medicinal herb residue into carbon materials lies in ensuring that the carbon materials obtained after treatment have a uniform nanostructure and stable properties.
[0004] With the development of science and technology, more and more biomass materials are being prepared and have high application potential. However, some of these require relatively complex preparation processes and stringent preparation conditions. Wu et al. (Chem. Phys. Lett., 2021, 139058) successfully prepared foam-like layered porous carbon (FHPCs) with well-developed mesopores and ultra-high specific surface area by combining Ca(OH)2 as a template precursor with KOH activation using petroleum asphalt as a raw material. Wang et al. (J. Alloys Compd., 2019, 109-117) successfully prepared porous carbon nanosheets with large specific capacitance by introducing NaOH as a co-activating agent in addition to KOH, using petroleum asphalt as a precursor. These commonly used chemical activation techniques often use too much highly corrosive activating agent, which can easily cause serious equipment corrosion and environmental pollution. Therefore, how to reduce the amount of activating agent used is also an important research direction. Summary of the Invention
[0005] The purpose of this invention is to provide an amination-modified porous carbon material, its preparation method, and its applications, effectively solving the technical problems involved in the background art. This invention uses plant-based medicinal herb residue, which has negative economic value, as raw material and optimizes existing activation technologies through internal crystallization with an activator. Subsequently, amino acids are used as raw materials to amination the porous carbon interface, reducing the covalent ion repulsion phenomenon during the electro-desalination process. Furthermore, the increased hydrophilicity of amino acids also improves the actual effective specific surface area of the material, addressing the problem of high specific surface area and low capacitance in previous technologies. The electrode material is then applied in both supercapacitor and capacitive desalination applications, demonstrating its excellent capacitance performance and broader economic development prospects. It also provides an effective strategy for the economical transformation of plant-based medicinal herb residue, which is toxic and difficult to classify.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0007] A method for preparing an aminated porous carbon material includes the following steps:
[0008] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 30-70g of KOH for 12 hours, then dry it at 60℃. Repeat this step 2-6 times after drying.
[0009] The selection of KOH quality is crucial. Too little KOH will result in insufficient activator wetting and low crystallization, failing to guarantee the occurrence of activation and pore-forming behavior. Too much KOH will waste activator and lead to over-crystallization, causing over-activation of the material, resulting in structural pulverization and a reduction in effective specific surface area. The same applies to the number of soaking cycles. Too few soaking cycles result in insufficient KOH crystallization within the bulk phase, leading to insufficient activation motive force and inadequate pore structure formation, which is detrimental to capacitance behavior. Too many soaking cycles result in excessive KOH crystals, leading to over-activation, collapse and fragmentation of the derived carbon structure, and a reduction in surface area, which is detrimental to the formation of double-layer capacitance and cycle stability.
[0010] 2) The material obtained above is carbonized at high temperature in a N2 atmosphere, with a heating rate of 1-3℃ / min. -1 The temperature was raised to 500-700℃ and held for 1.5 hours; after cooling, the sample was taken out and obtained by washing and drying with water to obtain black carbon material.
[0011] Among these factors, the heating conditions for carbonization are crucial. If the heating rate is too low, the carbonization efficiency will decrease, as will the activation efficiency of the activator. If the heating rate is too high, the biomass will rapidly pyrolyze, and the derived carbon will develop pyrolysis cracks, reducing structural stability. At the same time, the rapid pyrolysis of the activator will render the biomass ineffective in activating pore formation.
[0012] 3) Disperse the above carbon material in nitric acid for acidification, and keep it at a constant temperature of 50-70°C for 0.5-2 hours. After filtration, wash the carbon material with water until it is neutral, and collect the material after vacuum drying.
[0013] Among these factors, the acidification conditions are crucial. If the acidification temperature is too low, the acidification and oxidation process of nitric acid cannot proceed; if the acidification temperature is too high, the carbon interface will be over-oxidized, resulting in fragmentation. If the acidification time is too short, it will not be conducive to the uniformity of acidification; if the acidification time is too long, it will result in too many oxygen functional groups at the carbon interface, reducing the abundance of heteroatoms.
[0014] 4) Mix amino acids, N,N-dimethylformamide (used as a solvent), and acidified carbon material in a mass ratio of 7:1 to 12:1, stir, and transfer to a hydrothermal reactor. Maintain the temperature at 120℃ to 180℃ for 6 to 18 hours. After cooling, obtain the final sample by centrifugation, filtration, and drying.
[0015] The conditions of hydrothermal treatment are crucial. If the hydrothermal temperature is too low, amino acids cannot be well grafted onto the carbon material interface, especially the pore structure of the carbon material; if the hydrothermal temperature is too high, it will cause the amino acids at the carbon interface to deactivate and pyrolyze, reducing the modification effect.
[0016] Furthermore, the present invention also relates to aminated porous carbon materials prepared by the above method, and the application of the aminated porous carbon materials in supercapacitors and capacitor desalination equipment.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) By utilizing the hygroscopic properties of dried Chinese herbal medicine residue, the activator is adsorbed into the bulk phase of the material, ensuring the high efficiency of activation and pore formation, while also reducing the amount of activator used; this effectively reduces the cost and the environmental harm caused by strong alkali.
[0019] (2) The interface of amino acid functionalized carbon material can effectively alleviate the problem of covalent ion mutual repulsion in the capacitance behavior of carbon material, and also alleviate the problems of material oxidation and breakage caused by electric field.
[0020] (3) An effective and economical conversion strategy is provided for the Chinese medicine residue with complex composition and drug toxicity. Most of the Chinese medicine residue after use is a mixture of multiple drugs and often has certain medicinal properties, which are difficult to utilize. This invention provides an effective strategy for the treatment of waste Chinese medicine residue.
[0021] Meanwhile, this invention transforms Chinese herbal medicine residue into high specific surface area carbon material through crushing, soaking, drying and carbonization, and grafts hydrophilic amino acid functional groups onto the surface of the high specific surface area carbon material to enhance the hydrophilicity and pseudocapacitive properties of the material.
[0022] Regarding interface functional groups, firstly, amino acid-based interface functional groups can effectively enhance the wettability of materials, increase the actual effective area, and effectively improve the double-layer capacitance contribution of materials; secondly, amino functional groups can effectively alleviate the occurrence of side reactions such as co-ion repulsion and oxidative corrosion in capacitive behavior, and promote electron / ion transport; finally, amino functional groups can provide additional pseudocapacitive reactions, thereby increasing the capacitance of materials.
[0023] For versatility, this invention utilizes a soaking-activation method to transform complex-structured traditional Chinese medicine residue precursors into high-specific-surface-area derived carbon materials with a uniform structure; it leverages the water absorption and porosity of the traditional Chinese medicine residues to load the activator into the interior of the precursor; and the activation reaction occurs synergistically inside and outside the material at high temperature, ensuring the consistency of the material structure. The amination-modified porous carbon materials prepared by this invention exhibit excellent electrochemical performance in both supercapacitors and capacitor desalination equipment. Attached Figure Description
[0024] Figure 1 Here is a scanning electron microscope image of the carbon material synthesized in Example 1;
[0025] Figure 2 This is a transmission electron microscope (TEM) image of the carbon material synthesized in Example 1;
[0026] Figure 3 Here is a scanning electron microscope image of the carbon material synthesized in Example 2;
[0027] Figure 4 Here is a scanning electron microscope image of the carbon material synthesized in Example 3;
[0028] Figure 5 Here is a scanning electron microscope image of the carbon material synthesized in Example 4;
[0029] Figure 6 Here is a scanning electron microscope image of the carbon material synthesized in Example 5;
[0030] Figure 7 This is a transmission electron microscope (TEM) image of the carbon material synthesized in Example 6;
[0031] Figure 8 This is a transmission electron microscope (TEM) image of the carbon material synthesized in Example 5;
[0032] Figure 9 This is a nitrogen adsorption-desorption curve of the carbon material synthesized in Example 1;
[0033] Figure 10 The C spectrum of XPS, the carbon material synthesized in Example 1;
[0034] Figure 11 The N spectrum of XPS, the carbon material synthesized in Example 1;
[0035] Figure 12The O spectrum of XPS, the carbon material synthesized in Example 1;
[0036] Figure 13 This is a three-electrode cyclic voltammetry curve for Example 1;
[0037] Figure 14 This is a cyclic voltammetry curve of the three electrodes under different current rates in Example 1;
[0038] Figure 15 This is a three-electrode cyclic voltammetry curve for Example 5;
[0039] Figure 16 This is a three-electrode constant current charge-discharge diagram of Example 1;
[0040] Figure 17 The specific capacitance of Example 1 under different current densities;
[0041] Figure 18 The specific capacitance of Example 2 under different current densities;
[0042] Figure 19 Example 3 shows the specific capacitance under different current densities;
[0043] Figure 20 Example 4 shows the specific capacitance under different current densities;
[0044] Figure 21 Example 5 shows the specific capacitance under different current densities;
[0045] Figure 22 Example 6 shows the specific capacitance under different current densities;
[0046] Figure 23 The desalination capacity curve of Example 1 at 1.6V over time is shown.
[0047] Figure 24 The desalination capacity-desalination rate curve for Example 1 at 1.6V;
[0048] Figure 25 The CV curve of the symmetrical supercapacitor assembled in Example 1;
[0049] Figure 26 The power density-energy density curve of the symmetrical capacitor assembled in Example 1. Detailed Implementation
[0050] To make the objectives and advantages of this invention clearer, the invention will be specifically described below with reference to embodiments. It should be understood that the following text is merely used to describe one or more specific embodiments of the invention and does not strictly limit the scope of protection specifically claimed by the invention.
[0051] Example 1
[0052] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 50g of KOH for 12 hours, then dry it at 60℃; repeat this step 4 times after drying.
[0053] 2) The material obtained above was carbonized at high temperature in a N2 atmosphere at a heating rate of 1.5℃ / min. -1 The temperature was raised to 600℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0054] 3) Disperse the above carbon material in nitric acid and keep it at a constant temperature of 60°C for 1 hour; after filtration, wash the carbon material with water until it is neutral, dry it under vacuum and collect the material to obtain the acidified carbon material.
[0055] 4) Mix arginine, N,N-dimethylformamide (used as a solvent) and acidified carbon material in a mass ratio of 9:1, stir, and transfer to a hydrothermal reactor. Maintain the temperature at 120°C for 12 hours. After cooling, obtain the final sample by centrifugation, filtration and drying.
[0056] Figure 1 This is a scanning electron microscope (SEM) image of the carbon material synthesized in Example 1. Figure 1 It is evident that the activation method from the inside out makes the pore structure of carbon materials more uniform and abundant, with the potential for high specific surface area. Specifically, the pore structure of the carbon material synthesized in Example 1 is interconnected, forming a large cavity structure connected by small channels. Such a structure has a significant confinement effect, which will provide effective protection for the amino functional groups at the cavity interface.
[0057] Figure 2 This is a transmission electron microscope (TEM) image of the carbon material synthesized in Example 1. Figure 2 It is evident that the carbon layer is relatively thin, and the pore structure is uniformly distributed throughout the bulk phase of the material, which represents a higher specific surface area and a more suitable ion transport pathway.
[0058] Figure 9 This is a nitrogen adsorption-desorption curve of the carbon material synthesized in Example 1. (From...) Figure 9 It can be seen that carbon materials have a thickness as high as 1063.7m. 2 g -1 It has a large specific surface area; at the same time, it has a large number of channels below 10nm, which will promote the occurrence of double-layer capacitance behavior.
[0059] Figure 10 This is the C-chromatogram of XPS, the carbon material synthesized in Example 1. Figure 10It is evident that, in addition to the most prevalent C-C (284 eV) valence bonds, CN (285 eV), CO (286 eV), and C=O (288 eV) bonds also exist. The proportion of -C=O bonds is significantly higher than that of -CO bonds, likely due to the abundance of -C=O groups brought about by the grafted amino acid functional groups. This confirms the successful grafting of amino functional groups onto the carbon sheet surface, resulting in a rich and diverse array of oxygen-containing functional groups, which will provide abundant pseudocapacitive active sites.
[0060] Figure 11 This is the nitrogen spectrum of XPS, the carbon material synthesized in Example 1. Figure 11 It is evident that nitrogen (N) primarily originates from biomass precursors and amino acid functional groups, mainly in the form of doped heteroatoms and surface functional groups. Consistent with this, the N 1s fine spectrum shows three response peaks corresponding to pyridine-N (398.7 eV), pyrrole-N (399.7 eV), and graphite-N (400.9 eV), respectively. This is mainly due to N-doped defects derived from biomass precursors, which will contribute to pseudocapacitance. In addition, the N 1s fine spectrum also shows O=CN bonds (400.9 eV) and -NH2 (399.3 eV); O=CN originates from the digestion of carboxyl groups during amidation. The -NH2 originates from the unreacted portion of arginine, which will enhance the hydrophilicity of the material.
[0061] Figure 12 This is the O2 spectrum of XPS, the carbon material synthesized in Example 1. Figure 12 As can be seen, the O 1s spectrum can be divided into three peaks at 531.5 eV, 532.8 eV, and 534.2 eV, corresponding to -C=O, O=CO-, and -OCO-, respectively. The oxygen-containing functional groups will further enhance the wettability of the material and increase its effective specific surface area.
[0062] Example 2:
[0063] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 30g of KOH for 12 hours, then dry it at 60℃. Repeat this step 4 times after drying.
[0064] 2) The material obtained above was carbonized at high temperature in a N2 atmosphere at a heating rate of 1℃ / min. -1 The temperature was raised to 500℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0065] 3) Disperse the above carbon material in nitric acid and keep it at a constant temperature of 60°C for 1 hour. After filtration, wash the carbon material with water until neutral, dry it under vacuum, and collect the material to obtain the acidified carbon material.
[0066] 4) Arginine, N,N-dimethylformamide (used as a solvent), and acidified carbon material were mixed in a mass ratio of 9:1 and stirred. The mixture was then transferred to a hydrothermal reactor and kept at 120°C for 12 hours. After cooling, the final sample was obtained by centrifugation, filtration, and drying.
[0067] Figure 3 This is a scanning electron microscope (SEM) image of the carbon material synthesized in Example 2. Figure 3 It is evident that due to the small proportion of KOH, insufficient crystallization occurs in the precursor of traditional Chinese medicine residue, resulting in ineffective activation. Consequently, the pore structure is not abundant, and the low specific surface area is unfavorable for the occurrence of double-layer capacitance behavior.
[0068] Example 3:
[0069] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 70g of KOH for 12 hours, then dry it at 60℃. Repeat this step 4 times after drying.
[0070] 2) The material obtained above is carbonized at high temperature in a N2 atmosphere, with a heating rate of 1-3℃ / min. -1 The temperature was raised to 700℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0071] 3) Disperse the above carbon material in nitric acid and keep it at a constant temperature of 60°C for 1 hour. After filtration, wash the carbon material with water until neutral, dry it under vacuum, and collect the material to obtain the acidified carbon material.
[0072] 4) Arginine, N,N-dimethylformamide (used as a solvent), and acidified carbon material were mixed in a mass ratio of 9:1 and stirred. The mixture was then transferred to a hydrothermal reactor and kept at 120°C for 12 hours. After cooling, the final sample was obtained by centrifugation, filtration, and drying.
[0073] Figure 4 The image shows a scanning electron microscope (SEM) image of the carbon material synthesized in Example 3. As can be seen from the image, excessive KOH crystallization in the medicinal herb residue led to over-activation, resulting in significant fragmentation of the carbon material. This fragmentation then easily leads to agglomeration, reducing the material's effective specific surface area.
[0074] Example 4:
[0075] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 50g of KOH for 12 hours, then dry it at 60℃. Repeat this step 4 times after drying.
[0076] 2) The material obtained above was carbonized at high temperature in a N2 atmosphere at a heating rate of 3℃ / min. -1The temperature was raised to 700℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0077] 3) Disperse the above carbon material in nitric acid and keep it at a constant temperature of 60°C for 1 hour. After filtration, wash the carbon material with water until neutral, dry it under vacuum, and collect the material to obtain the acidified carbon material.
[0078] 4) Arginine, N,N-dimethylformamide (used as a solvent), and acidified carbon material were mixed in a mass ratio of 9:1 and stirred. The mixture was then transferred to a hydrothermal reactor and kept at 120°C for 12 hours. After cooling, the final sample was obtained by centrifugation, filtration, and drying.
[0079] Figure 5 This is a scanning electron microscope (SEM) image of the carbon material synthesized in Example 4. As can be seen from the image, due to the excessively rapid heating, the activator quickly entered the molten state, but this rapid rate resulted in uneven activation. The SEM reveals that activation mainly occurred on the surface of the carbon material, without the formation of a deep porous structure.
[0080] Example 5
[0081] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 50g of KOH for 12 hours, then dry it at 60℃. Repeat this step 4 times after drying.
[0082] 2) The material obtained above was carbonized at high temperature in a N2 atmosphere at a heating rate of 1.5℃ / min. -1 The temperature was raised to 600℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0083] 3) Disperse the above carbon material in nitric acid and keep it at a constant temperature of 60°C for 1 hour. After filtration, wash the carbon material with water until neutral, dry it under vacuum, and collect the material to obtain the acidified carbon material.
[0084] 4) Mix amino acids, N,N-dimethylformamide (used as a solvent), and acidified carbon material in a mass ratio of 9:1, stir, and transfer to a hydrothermal reactor. Maintain the temperature at 60°C for 12 hours. After cooling, obtain the final sample by centrifugation, filtration, and drying.
[0085] Figure 6 The image shows a scanning electron microscope (SEM) image of the carbon material synthesized in Example 5. As can be seen from the image, the nanostructure of the material is basically similar to that of Example 1. However, due to the low hydrothermal temperature, the reaction of arginine grafting onto the carbon interface did not occur sufficiently, and effective interface modification could not be formed.
[0086] Example 6
[0087] 1) Soak 10g of dried Chinese herbal medicine residue in a saturated solution containing 50g of KOH for 12 hours, then dry it at 60℃. Repeat this step 4 times after drying.
[0088] 2) The material obtained above was carbonized at high temperature in a N2 atmosphere at a heating rate of 1.5℃ / min. -1 The temperature was raised to 600℃ and held for 1.5 hours. After cooling, the sample was removed and obtained as black carbon material by washing and drying.
[0089] 3) Disperse the above carbon material in nitric acid and acidify it at a constant temperature of 80°C for 2 hours. After filtration, wash the carbon material with water until neutral, dry it under vacuum, and collect the material to obtain the acidified carbon material.
[0090] 4) Mix amino acids, N,N-dimethylformamide (used as a solvent), and acidified carbon material in a mass ratio of 9:1, stir, and transfer to a hydrothermal reactor. Maintain the temperature at 120°C for 12 hours. After cooling, obtain the final sample by centrifugation, filtration, and drying.
[0091] Figure 7 The image shows a transmission electron microscope (TEM) image of the carbon material synthesized in Example 6. As can be seen from the image, due to the excessively high acidification temperature, the carbon material was over-oxidized, resulting in severe fragmentation of the carbon sheet structure. In the TEM image, there are no obvious high aspect ratio structural sheets.
[0092] Application examples
[0093] Electrodes prepared in the above examples were subjected to supercapacitor and capacitor deionization tests respectively:
[0094] The prepared carbon material is used to fabricate a semi-capacitor device.
[0095] 1) The active material, namely carbon material, conductive graphite and binder polytetrafluoroethylene (PTFE), are mixed with an appropriate amount of ethanol in a mass ratio of 85:10:5 and then coated onto nickel foam (1cm×1cm) to obtain the working electrode.
[0096] 2) Dry the nickel foam working electrode in a 60°C oven to constant weight, and then press it under a pressure of 10MPa.
[0097] 3) Prepare the working electrode, reference electrode, counter electrode, salt bridge, and electrolyte, and assemble the semi-capacitor system.
[0098] The prepared carbon material is used to fabricate symmetrical capacitor devices.
[0099] 1) The active material, namely carbon material, conductive graphite and binder polytetrafluoroethylene (PTFE), are mixed with an appropriate amount of ethanol in a mass ratio of 85:10:5 and then coated onto nickel foam (1cm×1cm) to obtain the working electrode.
[0100] 2) Dry the nickel foam working electrode at 60°C to constant weight, and then press it into a pellet under a pressure of 10 MPa.
[0101] 3) Assemble a symmetrical capacitor by combining electrode sheets, diaphragms, and electrode solutions of equal mass.
[0102] The prepared carbon material was used to fabricate a capacitor deionization device.
[0103] 1) The symmetrical capacitor deionization device is assembled by coating the capacitor paste prepared above onto an electrode plate made of a 4cm×4cm titanium plate.
[0104] 2) The complete system includes a recovery container, a peristaltic pump, a CDI device, a DC power supply, and a conductivity meter for detecting the brine solution. Specific operating parameters are: the feed brine solution concentration is 200 mg / L. -1 500mg L -1 and 1000mg L -1 The flow rate was 32 mL / min. -1 ;
[0105] 3) The total volume of the salt solution is 80 mL; the applied potential differences are 1.0 V, 1.2 V, 1.4 V and 1.6 V; the solution temperature is 25 °C.
[0106] Figure 13 This is a three-electrode cyclic voltammetry curve for Example 1. Figure 13 It can be seen that: at 5mV s -1 The CV curves at various scan rates are nearly rectangular, indicating that its capacitive behavior is primarily characterized by double-layer capacitance. A slight peak is also observed on the CV curves, which is attributed to pseudocapacitive reactions derived from amino acid functional groups.
[0107] Figure 14 This is a cyclic voltammogram of the three electrodes under different current rates in Example 1. Figure 14 It can be seen that: at 5mV s -1 ~100mV s -1 Within the scanning range, its CV curve did not show obvious distortion, which means that it has good rate performance.
[0108] Figure 15 This is a three-electrode cyclic voltammetry curve for Example 5. (From...) Figure 15 It is evident that the amination was not significant due to the low temperature. The carbon material interface has fewer amino acid functional groups, and no redox peaks for amino functional groups appeared in the CV curve, resulting in a lower specific capacitance than in Example 1.
[0109] Figure 16 This is a three-electrode constant current charge-discharge diagram for Example 1. (From...) Figure 16 It can be seen that: at 0.5Ag-1 ~10Ag -1 Within a certain current density range, its GCD curves all exhibit slightly distorted isosceles triangles, indicating the coexistence of pseudocapacitive and double-layer capacitive behaviors. Its GCD curves all demonstrate near 100% Coulomb efficiency, proving that both its double-layer capacitive and pseudocapacitive behaviors are highly reversible.
[0110] Figure 17 The specific capacitance of Example 1 is shown under different current densities. Figure 17 It can be seen that: at 0.5Ag -1 At current densities of up to 306.6 F g, its specific capacitance can reach a maximum of 306.6 F g. -1 The specific capacitance decreases with increasing current density, due to insufficient reaction kinetics at the material surface and hindered ion diffusion at high current densities. However, even after a 20-fold increase in current density, the specific capacitance can still reach 73.3% of its original value.
[0111] Figure 18 This refers to the specific capacitance under different current densities in Example 2. Figure 18 It can be seen that due to insufficient activation in Example 2, the material has a low specific surface area, exhibits a low specific capacitance, and has a weak capacitance capability.
[0112] Figure 19 This refers to the specific capacitance under different current densities in Example 3. Figure 19 It can be seen that the carbon material agglomerates due to excessive KOH activation, and the specific capacitance of the carbon material is lower than that in Example 1.
[0113] Figure 20 This refers to the specific capacitance under different current densities in Example 4. Figure 20 It is evident that due to excessively rapid heating, the activator is insufficient to quickly construct a deep pore structure, which is detrimental to the occurrence of dual-cell capacitor behavior.
[0114] Figure 21 This refers to the specific capacitance under different current densities in Example 5. Figure 21 It is evident that, due to the lack of amino functional groups in the pseudocapacitance, its specific capacitance is lower than that of Example 1. However, due to the high reversibility and high power of the double-layer capacitor, its rate performance is better.
[0115] Figure 22 This refers to the specific capacitance of Example 6 under different current densities. (From...) Figure 22 It is evident that high-temperature acidification leads to excessive oxidation of carbon materials, resulting in an excessive number of functional groups and significant structural fragmentation, thus reducing specific capacitance. Furthermore, the high proportion of pseudocapacitors also reduces rate performance.
[0116] Figure 23This is the desalination capacity curve of Example 1 at 1.6V over time. (From...) Figure 23 It is evident that when a voltage of 1.6V is applied, the conductivity of the salt solution in which it is located decreases rapidly, due to the rapid response of the high-efficiency capacitor. The adsorption capacity of the corresponding electrode material continuously increases, reaching equilibrium within 15 minutes. The salt adsorption capacity of the carbon material reaches as high as 33.23 mg g. -1 Its high specific surface area and hydrophilicity promote capacitive behavior and enhance its ability to adsorb charged ions.
[0117] Figure 24 This is the desalination capacity-desalination rate curve for Example 1 at 1.6V. (From...) Figure 24 It is evident that it exhibits a relatively good salt adsorption rate. This is mainly because the preparation of carbon materials in step 1 still primarily relies on double-layer capacitance behavior.
[0118] Figure 25 The CV curve is shown for the symmetrical supercapacitor assembled in Example 1. Figure 25 It can be seen that: in the range of 5–100 mV s -1 Within the scanning rate range, its CV curve exhibits a quasi-rectangular shape without significant distortion. This quasi-rectangular CV shape indicates that its energy storage behavior is primarily characterized by double-layer capacitance, supplemented by pseudocapacitive behavior, and it possesses good rate performance. This is mainly attributed to its highly open porous structure and efficient charge transfer capability.
[0119] Figure 26 The power density-energy density curve is shown for the symmetrical capacitor assembled in Example 1. Figure 26 It can be seen that its maximum power density and energy density can reach 2500 W kg. -1 and 8.8Wh kg -1 It exhibits superior performance.
[0120] This patent utilizes an impregnation crystallization method to immerse an activator into the bulk phase of a biomass precursor, achieving a synergistic activation effect both internally and externally, thus creating a high specific surface area structure with interconnected internal and external cavities. Simultaneously, hydrophilic amino acid functional groups optimize the electrolyte wetting efficiency of the material, increasing the effective specific surface area. Furthermore, the amino acid functional groups suppress side reactions such as co-ion repulsion and oxidative corrosion, improving the material's cycle stability. The confinement effect of the cavities in the carbon material effectively protects the attachment of the amino acid functional groups, achieving a synergistic optimization effect. Therefore, it exhibits excellent capacitive performance, demonstrating superior performance in both supercapacitor and capacitor desalination applications.
[0121] The embodiments of the present invention have been described in detail above with reference to the examples. However, the present invention is not limited to the above embodiments. For those skilled in the art, after learning the contents described in the present invention, several equivalent changes and substitutions can be made without departing from the principle of the present invention. These equivalent changes and substitutions should also be considered to fall within the protection scope of the present invention.
Claims
1. A method for preparing an aminated porous carbon material, characterized in that, Includes the following steps: S1. After drying the Chinese herbal medicine residue, crush it, then soak the crushed residue in a saturated potassium hydroxide solution and let it stand in a vacuum environment for 3-5 hours, and then freeze-dry it; repeat the above steps until potassium hydroxide crystals appear inside the Chinese herbal medicine residue; wherein, the mass ratio of Chinese herbal medicine residue to saturated potassium hydroxide solution is 1:3 to 1:7; the number of repetitions is 2 to 5. S2. The product obtained in step S1 is carbonized at high temperature in a N2 atmosphere to obtain carbon material. After cooling, the carbon material is washed with water and dried to obtain carbon material. S3. Disperse the carbon material in nitric acid for acidification, and then wash the acidified carbon material until the pH is neutral; wherein, the carbon material is acidified in nitric acid at a temperature of 50 ~ 70℃ for a time of 0.5 ~ 2 h; S4. Arginine and acidified carbon material are subjected to hydrothermal treatment. After the material is cooled, it is centrifuged, washed and dried to obtain aminated porous carbon material.
2. The method for preparing aminated porous carbon material according to claim 1, characterized in that: The mass ratio of Chinese herbal medicine residue to saturated potassium hydroxide solution is 1:
5.
3. The method for preparing aminated porous carbon material according to claim 1, characterized in that: In step S2, the high-temperature carbonization heating rate is 1 ~ 3℃ min. -1 Heat to 500-700℃ and hold at that temperature for 1-2 hours.
4. The method for preparing aminated porous carbon material according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step S4 is 120℃ ~ 180℃, and the time is 6 ~ 18 h.
5. The method for preparing aminated porous carbon material according to claim 1, characterized in that: The mass ratio of arginine to carbon material is 7:1 to 12:
1.
6. An aminated porous carbon material, characterized in that: It is prepared by the preparation method according to any one of claims 1-5.
7. The application of the amination porous carbon material according to claim 6 in supercapacitors and capacitor desalination equipment.
Citation Information
Patent Citations
Method for preparing high-specific-capacity supercapacitor through durian shell
CN106115695A
Method for one-step preparation of sulfur-nitrogen-doped cotton-based porous carbon
CN107275640A